1996
DOI: 10.1590/s0034-89101996000500004
|View full text |Cite
|
Sign up to set email alerts
|

Sistema computacional para índices de cárie dentária: banco de dados e análise estatística

Abstract: ResumoApresenta-se um sistema computacional, denominado ICADPLUS, desenvolvido para elaboração de banco de dados, tabulação de dados, cálculo do índice CPO e análise estatística para estimação de intervalos de confiança e comparação de resultados de duas populações.Tem como objetivo apresentar método simplificado para atender necessidades de serviços de saúde na área de odontologia processando fichas utilizadas por cirurgiões dentistas em levantamentos epidemiológicos de cárie dentária. A característica princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Similarly, research analyzing the content and usability of mobile oral health applications found that dental application studies are comparatively small and that only a limited number of screening and diagnostic applications have been developed for research, practice management, dental education and scheduling [32]. In Brazil, research similar to the one that developed NutriOdonto was conducted by Sundefeld and Gotlieb [34]. These researchers presented a computer system, called ICADPLUS, developed for database elaboration, data tabulation, CPO index calculation and statistical analysis for confidence interval estimation and comparison of results of two populations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research analyzing the content and usability of mobile oral health applications found that dental application studies are comparatively small and that only a limited number of screening and diagnostic applications have been developed for research, practice management, dental education and scheduling [32]. In Brazil, research similar to the one that developed NutriOdonto was conducted by Sundefeld and Gotlieb [34]. These researchers presented a computer system, called ICADPLUS, developed for database elaboration, data tabulation, CPO index calculation and statistical analysis for confidence interval estimation and comparison of results of two populations.…”
Section: Discussionmentioning
confidence: 99%